Progressive grey matter atrophy over the first 2–3 years of illness in first-episode schizophrenia: A tensor-based morphometry study - Whitford, Thomas J.; Grieve, Stuart M.; Farrow, Tom F.D.; Gomes, Lavier; Brennan, John; Harris, Anthony W.F.; Gordon, Evian; Williams, Leanne M. (NeuroImage (Orlando, Fla.), 2006)
Little is known about the structural brain changes that occur over the first few years of schizophrenia, or how these changes differ from those associated with healthy brain development in adolescence and early adulthood. In this study, we aimed to identify regional differences in grey matter (GM) volume between patients with first-episode schizophrenia (FES) and matched healthy controls, both at the time of the patients' first psychotic episode (baseline condition) and 2–3 years subsequently (follow-up condition). Forty-one patients with FES and 47 matched healthy controls underwent a T1-weighted structural MRI scan. Of these participants, 25 FES patients and 26 controls returned 2–3 years later for a follow-up scan. Voxel-based morphometry in SPM2 was used to identify the regions of GM difference between the groups in the baseline condition, while tensor-based morphometry was used to identify the longitudinal change within subject over the follow-up interval. The FES patients exhibited widespread GM reductions in the frontal, parietal, and temporal cortices and cerebellum in the baseline condition, as well as more circumscribed regions of GM increase, particularly in the occipital lobe. Furthermore, the FES subjects were observed to lose considerably more GM over the follow-up interval than the controls, especially in the parietal and temporal cortices. We argue that the progressive GM atrophy we have found to be associated with the onset of schizophrenia arises from a dysfunction in the dramatic period of healthy brain development typically associated with adolescence.